(3x-7)(4x-5)=

Simple and best practice solution for (3x-7)(4x-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-7)(4x-5)= equation:


Simplifying
(3x + -7)(4x + -5) = 0

Reorder the terms:
(-7 + 3x)(4x + -5) = 0

Reorder the terms:
(-7 + 3x)(-5 + 4x) = 0

Multiply (-7 + 3x) * (-5 + 4x)
(-7(-5 + 4x) + 3x * (-5 + 4x)) = 0
((-5 * -7 + 4x * -7) + 3x * (-5 + 4x)) = 0
((35 + -28x) + 3x * (-5 + 4x)) = 0
(35 + -28x + (-5 * 3x + 4x * 3x)) = 0
(35 + -28x + (-15x + 12x2)) = 0

Combine like terms: -28x + -15x = -43x
(35 + -43x + 12x2) = 0

Solving
35 + -43x + 12x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(5 + -4x)(7 + -3x) = 0

Subproblem 1

Set the factor '(5 + -4x)' equal to zero and attempt to solve: Simplifying 5 + -4x = 0 Solving 5 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -4x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = 0 + -5 -4x = 0 + -5 Combine like terms: 0 + -5 = -5 -4x = -5 Divide each side by '-4'. x = 1.25 Simplifying x = 1.25

Subproblem 2

Set the factor '(7 + -3x)' equal to zero and attempt to solve: Simplifying 7 + -3x = 0 Solving 7 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = 0 + -7 -3x = 0 + -7 Combine like terms: 0 + -7 = -7 -3x = -7 Divide each side by '-3'. x = 2.333333333 Simplifying x = 2.333333333

Solution

x = {1.25, 2.333333333}

See similar equations:

| 1/7y=1 | | (-x^2)-2x=0 | | (7+V)(3v-8)=0 | | log(7x+1)=3 | | 5x+4(5x-7)=122 | | (10y-15)/3y=3 | | 8v^2+5=41v | | 2x+6(2x-4)=116 | | y=100+8.25(1) | | t^2-27t=0 | | 5a=51+2a | | 5x=15y-30 | | 5/11=u/12 | | 9.(-5/3)= | | 4x^2+4y^2-6x+8y-10=0 | | 2(m+1)-2m=0 | | X=2x-2.5 | | 5(8x-3)+25=180 | | 3n^2=-5n | | (u-1)(u+8)=x | | 9.75=100+8.25*1 | | 125000-62500=0.25y | | sqrt(x+23)+sqrt(2-x)=sqrt(-2x-1) | | 18/5a=3/5 | | 16/11*-18/36 | | y=100+8.25x | | -7/8-1/2= | | 10x-36=180 | | 6/7=3z/42 | | 5(2x+1)-7(x-2)=-1 | | x+(x+1)+(x*2)=29 | | x^3+0.6x^2-13.4x+3.9=0 |

Equations solver categories